2020
DOI: 10.1002/ajmg.a.61806
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlation of 33 patients with maple syrup urine disease

Abstract: Maple syrup urine disease (MSUD) is a rare autosomal recessive inherited disorder due to defects in the branched-chain α-ketoacid dehydrogenase complex (BCKDC). MSUD varies in severity and its clinical spectrum is quite broad, ranging from mild to severe phenotypes. Thirty-three MSUD patients were recruited into this study for molecular genetic variant profiling and genotype-phenotype correlation. Except for one patient, all other patients presented with the classic neonatal form of the disease. Seventeen diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…In terms of genetic variants detected, the proportion of patients with biallelic variants in BCKDHB is much larger than the reported in the Mennonite population (Strauss et al, 2020). Malaysian, Egyptian and Brazilian populations also show a predominance of biallelic variants in BCKDHB, being associated with 45-55% MSUD cases (Ali & Ngu, 2018;Khalifa et al, 2020;Margutti et al, 2020). Nevertheless, our population shows an even higher frequency of these variants.…”
Section: Discussioncontrasting
confidence: 61%
“…In terms of genetic variants detected, the proportion of patients with biallelic variants in BCKDHB is much larger than the reported in the Mennonite population (Strauss et al, 2020). Malaysian, Egyptian and Brazilian populations also show a predominance of biallelic variants in BCKDHB, being associated with 45-55% MSUD cases (Ali & Ngu, 2018;Khalifa et al, 2020;Margutti et al, 2020). Nevertheless, our population shows an even higher frequency of these variants.…”
Section: Discussioncontrasting
confidence: 61%
“…Unlike other cohorts, such as the old order Mennonites and Filipino cohorts, the Irish cohort is genetically quite heterogeneous, including genotypes which had not been hitherto reported. Additionally when compared to other recent cohort studies conducted in Spain, Egypt and Brazil where a large burden of disease was attributable to consanguinity (22.7%‐88% of patients described), 19‐21 there was limited evidence of consanguinity, although one included family (n = 2) were of Irish‐Traveller descent which as previously described has a low level of genetic heterogeneity 22 …”
Section: Discussionmentioning
confidence: 72%
“…The clinical manifestations of patients with DBT gene variant are relatively mild, but in this study, two classical patients who carried DBT homozygous mutations, both with neonatal onset and death, were classic MUSD patients. A previous study reported that a classical patient with the c.1291C>T (p.R431*) homozygous mutation died at six months (Khalifa et al, 2020). The report indicated that another patient who carried the c.1291C>T (p.R431*) homozygous mutation was diagnosed four days after birth with feeding difficulties and seizure symptoms, diagnosed as MSUD (Abiri et al, 2019).…”
Section: Discussionmentioning
confidence: 98%